Digital Empowerment Through Artificial Intelligence And Financial Literacy: Evidence From Women Owned MSMEs In Makassar, Indonesia - Indah Lestari Anwar; Fakhirah Husain; Muhammad Fakhrul Anwar (International Journal of Education Management and Religion, 2026)
This study examines the role of artificial intelligence (AI) and digital financial literacy in sustaining women-owned micro, small, and medium enterprises (MSMEs) in Makassar City, Indonesia. Using a mixed-methods approach with an explanatory sequential design, this research combines qualitative exploration with quantitative testing through Structural Equation Modeling–Partial Least Squares (SEM-PLS) with a purposive sample of 150 respondents drawn from 3,060 women-owned MSMEs registered with the MSME Incubator in Makassar. The Digital Empowerment model proposed in this study refers to an integrated framework in which AI and digital financial literacy work complementarily to strengthen business decision-making, financial behavior, and fintech adoption among women-owned MSMEs. The results show that AI has a positive and significant direct effect on MSME sustainability, as does financial literacy. Financial behavior and financial technology were found to significantly mediate the relationship between financial literacy and MSME sustainability — confirming both indirect pathways. However, neither financial behavior nor financial technology significantly mediated the AI–sustainability relationship, indicating that AI's impact remains direct at this stage of adoption. These findings carry important practical implications: local governments and MSME incubators should develop integrated digital financial literacy training programs that incorporate AI-based decision-support tools. This study makes a novel theoretical contribution by proposing an operational Digital Empowerment model contextualized for women-owned MSMEs in Eastern Indonesia, filling a gap in the empirical literature on AI adoption and MSME sustainability in developing countries.